2017
DOI: 10.1021/acs.biochem.7b00943
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Biosynthetic Pathway for the Antibiotic Bicyclomycin

Abstract: Diketopiperazines (DKPs) make up a large group of natural products with diverse structures and biological activities. Bicyclomycin is a broad-spectrum DKP antibiotic with unique structure and function: it contains a highly oxidized bicyclic [4.2.2] ring and is the only known selective inhibitor of the bacterial transcription termination factor, Rho. Here, we identify the biosynthetic gene cluster for bicyclomycin containing six iron-dependent oxidases. We demonstrate that the DKP core is made by a tRNA-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 28 publications
5
59
0
1
Order By: Relevance
“…We extended our analysis to all CDPSs biochemically characterized to date. This set now consists of 98 active CDPSs (Gondry et al, 2009 ; Seguin et al, 2011 ; Giessen et al, 2013a , b ; Alqahtani et al, 2015 ; Jacques et al, 2015 ; James et al, 2016 ; Brockmeyer and Li, 2017 ; Patteson et al, 2017 ). The products and P1 and P2 motifs of all the enzymes previously characterized are shown in blue in Supplemental Data Set 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We extended our analysis to all CDPSs biochemically characterized to date. This set now consists of 98 active CDPSs (Gondry et al, 2009 ; Seguin et al, 2011 ; Giessen et al, 2013a , b ; Alqahtani et al, 2015 ; Jacques et al, 2015 ; James et al, 2016 ; Brockmeyer and Li, 2017 ; Patteson et al, 2017 ). The products and P1 and P2 motifs of all the enzymes previously characterized are shown in blue in Supplemental Data Set 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The number of characterized biosynthetic pathways for DKPs is relatively low relative to their known diversity (Belin et al, 2012 ; Giessen and Marahiel, 2015 ). Ten pathways that involve NRPSs have been decoded (Belin et al, 2012 ; Giessen and Marahiel, 2015 ), whereas only six have been shown to depend on CDPSs: albonoursin (Lautru et al, 2002 ), pulcherrimin (Cryle et al, 2010 ), mycocyclosin (Belin et al, 2009 ), methylated ditryptophan (Giessen et al, 2013a ), nocazines (Giessen et al, 2013b ), and, most recently bicyclomycin (Meng et al, 2017 ; Patteson et al, 2017 ). In this context, mapping the diversity of cyclodipeptides attainable by CDPSs allows the identification of new gene clusters responsible for the synthesis of DKPs with high pharmacological potential, as illustrated by the recent identification of the biosynthetic pathway of bicyclomycin, which involves a CDPS predicted to belong to the cLI/cLL-synthesizing group (Patteson et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, CDPSs generally occur associated with tailoring enzymes 15 . Nonetheless only four CDPS-dependent pathways have been fully understood so far, including albonoursin 7 , 16 , nocazines 17 , 18 , pulcherriminic acid 19 , and bicyclomycin 20 , 21 . Compared to the canonic NRPS pathways, CDPS pathways are still underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…287 One of the more impressive series of transformations reported to occur during bacterial DKP synthesis is found in the biosynthesis of bicyclomycin. 293,294 In this pathway, the initial cyclo(L-Leu-L-Ile) DKP undergoes six oxidation events (catalysed by ve a-ketoglutarate/Fe 2+ -dependant dioxygenases (BcmB/C/E/F/G) and one cytochrome P450 (BcmD)) to afford the nal, bicyclic structure of bicyclomycin. Within this pathway, the BcmD has been identied as carrying out the penultimate oxidation reaction, which affords hydroxylation of the C6 position of the DKP ring (Fig.…”
mentioning
confidence: 99%